Norman Dott: three vignettes on the making of a master neurosurgeon. (3rd May 2020) - Ah-See, Rowan C. W.; Wright, David; Demetriades, Andreas K.
Abstract: Purpose: This historical perspective paper attempts to provide a unique picture of Norman Dott through three vignettes from periods of his life and career. Materials and methods: Archive materials relating to Norman Dott in the Lothian Health Service Archive and the University of Edinburgh's Centre for Research Collections, including letters, notes and speeches, were consulted and provide the principle sources supporting this paper. Additional materials including books and journal articles written by or about Dott were accessed while writing this paper. Results and conclusions: Norman Dott CBE FRCSE FRSE FRCSC (1897–1973) is now considered one of the most influential surgeons of his generation. During a 44-year career he was a pioneer of transsphenoidal pituitary surgery, craniopharyngioma surgery, intracranial aneurysm surgery and other neurosurgical topics. The historical vignettes explored in this paper illuminate certain aspects of Dott's life, career and character that had an important impact on his achievements in neurosurgery.